Association of intraindividual tacrolimus variability with de novo donor-specific HLA antibody development and allograft rejection in pediatric kidney transplant recipients with low immunological risk - Baghai Arassi, Maral; Gauche, Laura; Schmidt, Jeremy; Höcker, Britta; Rieger, Susanne; Süsal, Caner; Tönshoff, Burkhard; Fichtner, Alexander (Pediatric nephrology, 2022)
Tacrolimus (Tac) intraindividual variability (TacIPV) in pediatric kidney transplant patients is only poorly understood. We investigated the impact of TacIPV on de novo donor-specific HLA antibodies (dnDSA) development and allograft rejection in Caucasian pediatric recipients of a living or deceased donor kidney with low immunological risk.